2014
DOI: 10.2136/sssaj2013.09.0413nafsc
|View full text |Cite
|
Sign up to set email alerts
|

Litter Input Controls on Soil Carbon in a Temperate Deciduous Forest

Abstract: Above‐ and belowground litter inputs in a temperate deciduous forest were altered for 20 yr to determine the importance of leaves and roots on soil C and soil organic matter (SOM) quantity and quality. Carbon and SOM quantity and quality were measured in the O horizon and mineral soil to 50 cm in five treatments (control, double litter [DL], no litter [NL], no roots [NR], no inputs [NI]). After two decades of doubled litter addition, soil C and SOM did not increase. However, leaf litter exclusions reduced soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 54 publications
7
69
0
Order By: Relevance
“…This is similar to results found in a temperate deciduous DIRT site in Massachusetts (USA), where C concentrations decreased within the first decade of experimental litter reductions (Nadelhoffer et al, 2004), and which were more pronounced after two decades (Lajtha et al, 2013a). Similar soil C reductions were observed in two other DIRT experiments in deciduous temperate forests in Allegheny College Bousson Environmental Research Reserve (USA) and University of Wisconsin Arboretum (USA) (Bowden et al, 2013, Lajtha et al, 2013b. The two root exclusion treatments showed greater losses of soil C than those observed in the NL treatment in the 5-15 cm soil layer, demonstrating the critical role of belowground C supply to controlling soil C accumulation in this forest, as has been demonstrated elsewhere (Makkonen and Helmisaari, 2001;Rasse et al, 2005;Fekete et al, 2011a).…”
Section: Changes In Soil Total Carbon Concentrationsupporting
confidence: 81%
See 1 more Smart Citation
“…This is similar to results found in a temperate deciduous DIRT site in Massachusetts (USA), where C concentrations decreased within the first decade of experimental litter reductions (Nadelhoffer et al, 2004), and which were more pronounced after two decades (Lajtha et al, 2013a). Similar soil C reductions were observed in two other DIRT experiments in deciduous temperate forests in Allegheny College Bousson Environmental Research Reserve (USA) and University of Wisconsin Arboretum (USA) (Bowden et al, 2013, Lajtha et al, 2013b. The two root exclusion treatments showed greater losses of soil C than those observed in the NL treatment in the 5-15 cm soil layer, demonstrating the critical role of belowground C supply to controlling soil C accumulation in this forest, as has been demonstrated elsewhere (Makkonen and Helmisaari, 2001;Rasse et al, 2005;Fekete et al, 2011a).…”
Section: Changes In Soil Total Carbon Concentrationsupporting
confidence: 81%
“…After 20 years, soil C in litter exclusion and root exclusion plots showed similar declines in an oak forest (Harvard Forest, Massachusetts, USA (Lajtha et al, 2013b)). Soil C reduced to a greater extent in a litter exclusion treatment than in a root exclusion treatment in a black cherry-sugar maple forest (Bousson Environmental Research Reserve, Pennsylvania, USA) (Bowden et al, 2013). It is not clear what controls the relative importance of aboveground and belowground litter contributions to soil C. Root and leaf litter decompose at different rates (Hobbie et al, 2010), and may produce different organic compounds that undergo different rates of chemical (Hassink, 1997) and physical (Six et al, 2002, Pronk et.…”
Section: Changes In Soil Total Carbon Concentrationmentioning
confidence: 99%
“…In the north central USA, soil C content decreased by 44 % in litter removal plots and increased by 31 % in double litter plots over a 50-year period ( Table 2 in Lajtha et al, 2014a). In Pennsylvania, USA, 20 years of removing litter reduced soil C by 24 %, although the corresponding litter doubling had no effect (Bowden et al, 2014). In a deciduous forest in Massachusetts, USA, 20 years of litter removal also reduced mineral soil C (by 19 %), but litter addition also resulted in lower mineral soil C (by 6 %, Lajtha et al, 2014b).…”
Section: Soil Carbon Dynamicsmentioning
confidence: 99%
“…Soil C has been shown to respond to experimental changes in litter inputs. In three studies in temperate forests in the USA, litter removal always resulted in lower soil organic carbon, but litter addition had much more variable effects, increasing in one (Lajtha et al, 2014a), not changing in the second (Bowden et al, 2014) and decreasing in the third (Lajtha et al, 2014b). The single study from the tropics, in lowland rain forest in southwestern Costa Rica, reported decreased soil C in litter removal plots and increased soil C in litter addition plots (Leff et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…It is not clear how plant litter quantity and quality and source (i.e., roots versus aboveground litter) are linked to C retention in soils (Dungait et al, ; Lajtha, Bowden, & Nadelhoffer, ; Lajtha, Townsend, et al, ). Thus, the potential to sequester additional C within soils through management remains speculative (Dungait et al, ), especially as C addition may potentially “prime” decomposition of native C stocks (Bowden et al, ; Kuzyakov, ; Lajtha, Bowden, & Nadelhoffer, ; Lajtha, Townsend, et al, ). To predict, and possibly manipulate, soil‐climate feedbacks, we must understand the pathways C takes through soil, from the incorporation and transformation of litter inputs to its ultimate mineralization.…”
Section: Introductionmentioning
confidence: 99%